Mental health among older refugees: the role of trauma, discrimination, and religiousness. (3rd August 2017) - Mölsä, Mulki; Kuittinen, Saija; Tiilikainen, Marja; Honkasalo, Marja-Liisa; Punamäki, Raija-Leena
ABSTRACT: Objectives: The aim of this study was to examine, first, how past traumatic stress and present acculturation indices, and discrimination are associated with mental health; and, second, whether religiousness can buffer the mental health from negative impacts of war trauma. Method: Participants were 128 older (50–80 years) Somali refugees living in Finland. They reported experiences of war trauma and childhood adversities, and filled-in questionnaires of perceived ethnic discrimination, religiousness (beliefs, attendance, and observance of Islamic faith), and symptoms of posttraumatic stress disorder (PTSD), depressive (BDI-21), psychological distress (GHQ-12), and somatization (SCL-90). Results: Symptom-specific regression models showed that newly arrived refugees with non-permanent legal status and severe exposures to war trauma, childhood adversity, and discrimination endorsed greater PTSD symptoms, while only war trauma and discrimination were associated with depressive symptoms. Results confirmed that high religiousness could play a buffering role among older Somalis, as exposure to severe war trauma was not associated with high levels of PTSD or somatization symptoms among highly religious refugees. Conclusion: Health care should consider both unique past and present vulnerabilities and resources when treating refugees, and everyday discrimination and racism should be regarded as health risks.